2013
DOI: 10.1124/jpet.113.209916
|View full text |Cite
|
Sign up to set email alerts
|

No Activation of Human Pregnane X Receptor by Hyperforin-Related Phloroglucinols

Abstract: The acylated phloroglucinol, hyperforin, the main active ingredient of St. John's Wort, exerts antidepressant properties via indirect inhibition of serotonin reuptake by selectively activating the canonical transient receptor potential channel 6 (TRPC6). Hyperforin treatment can lead to drug-drug interactions due to potent activation of the nuclear receptor PXR (NR1I2), a key transcriptional regulator of genes involved in drug metabolism and transport. It was previously shown that synthetic acylated phlorogluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…Hyperforin increased the Ca 2+ influx by activating or upregulating TRPC6 channels, and possibly increased the ATP release through mechanosensitive hemichannels, although the underlying mechanism remains to be elucidated. Hyperforin is known to exert a variety of effects on cells, including activation of the pregnane X nuclear receptor (PXR) (Moore et al, 2000, Kandel et al, 2014. In our HaCaT cell system, hyperforin treatment resulted in reduced cell proliferation and a decreased basic Ca 2+ influx (non-stimulated or non-TRPC6), but did not affect the expression level of ATP receptors (e.g.…”
Section: Fig 7 the Inhibitory Effects Of Various Inhibitors Of Atp-camentioning
confidence: 90%
“…Hyperforin increased the Ca 2+ influx by activating or upregulating TRPC6 channels, and possibly increased the ATP release through mechanosensitive hemichannels, although the underlying mechanism remains to be elucidated. Hyperforin is known to exert a variety of effects on cells, including activation of the pregnane X nuclear receptor (PXR) (Moore et al, 2000, Kandel et al, 2014. In our HaCaT cell system, hyperforin treatment resulted in reduced cell proliferation and a decreased basic Ca 2+ influx (non-stimulated or non-TRPC6), but did not affect the expression level of ATP receptors (e.g.…”
Section: Fig 7 the Inhibitory Effects Of Various Inhibitors Of Atp-camentioning
confidence: 90%
“…However, considering that drug elimination is based on an interplay of multiple mechanisms, increased clearance can only be achieved if phase I and phase II biotransformation and cellular efflux are modulated at the same time (Figure ). Testing the influence of in vitro treatment with hyperforin on the mRNA expression in human hepatocytes revealed significantly enhanced expression of CYP2B6, CYP2C9, CYP3A4, CYP3A5, UGT1A1, and ABCB1 (Kandel et al, ). For CYP2B6, Goodwin et al had previously shown the binding of PXR to the promotor.…”
Section: Pxr‐mediated Transcriptional Regulation Of a Drug Metabolizimentioning
confidence: 99%
“…1d) blocked serotonin uptake in murine synaptosomes and were able to mimic nearly all features shown for hyperforin, e.g., induction of neurite growth and TRPC6 activation [ (Leuner et al 2010) for further aspects see below]. However, the absence of PXR binding is the most impressive feature of the 2,4-diacylphloroglucinol compounds (Kandel et al 2014). Docking studies, modeling the compounds into the crystal structure of PXR provided evidence for the inefficiency of the compounds to bind to PXR (Kandel et al 2014).…”
Section: Hyperforin As Protonophorementioning
confidence: 99%
“…However, the absence of PXR binding is the most impressive feature of the 2,4-diacylphloroglucinol compounds (Kandel et al 2014). Docking studies, modeling the compounds into the crystal structure of PXR provided evidence for the inefficiency of the compounds to bind to PXR (Kandel et al 2014). The modeling results could be validated by biochemical experiments testing the induction of the expression of drug metabolizing proteins.…”
Section: Hyperforin As Protonophorementioning
confidence: 99%
See 1 more Smart Citation